Corporate Governance Mechanisms, Profitability, Company Size and Tax Avoidance : (Empirical Studies on Manufacturing Companies in Indonesia and Malaysia from 2015-2018) - Andriani, Novia; Haryono, Slamet (Journal of Accounting Inquiry, 2022)
Purpose: This research examines the impact of corporate governance mechanisms, profitability, and company size on tax avoidance. Methodology: This research uses multiple regression analysis and an independent sample t-test. Based on a sample of 380 firm-year observations from 95 manufacturing companies listed on the List of Sharia-Compliant Securities in Indonesia and Malaysia in 2015-2018. Findings: The results of this research concludes that independent of the boards, audit committees, audit quality, institutional ownership and managerial compensation had negative influences on tax avoidance. Profitability and company size had positive influences on tax avoidance. This research also finds differences in the level of tax avoidance in Indonesia and Malaysia. Novelty: This study uses manufacturing companies in Indonesia and Malaysia from 2015-2018